Effects of salt, moisture content and microwave power on puffing qualities of puffed rice - Maisont, Suchada; Narkrugsa, Woatthichai (My University, 2010)
In this study, the effects of salt, moisture content and microwave power on the puffing qualities of puffed rice were investigated. Paddy rice was adjusted with water and 2% salt solution at four moisture levels 10, 13, 16 and 19% (wb) and puffed with microwave power at 600, 700 and 800 watts. The results showed that all the main factors and their interactions significantly (p<0.05) affected the puffing qualities of total puffed yield, fully puffed yield, small puffed yield, expansion volume, texture, color and microstructure. Paddy rice soaked in 2% salt solution produced a higher puffed yield than paddy rice soaked in water. Higher moisture content and microwave power produced puffed rice with higher puffed yield and expansion volume, but lower hardness. Puffing paddy rice at low moisture content (10%) with low microwave power (600 watts) produced the hardest puffed rice texture. Puffing at low moisture content and high wattage decreased the lightness of the puffed rice. Puffing paddy rice at 19% moisture content with 600-700 watts produced the highest fully puffed yield, but the lowest total puffed yield. The results suggested that high puffed yield and expansion volume with moderate hardness was produced using soaked paddy rice at 2% salt solution, 13% moisture content and puffed with 700 or 800 watts microwave power.
Keywords: Microwave; Microwave puffing; Puffed rice; Puffing